Experimental performance of irregular PZs in CHS column H-shape beam steel frame. (July 2019) - Sui, Weining; Wang, Zhanfei; Li, Xiaomin
Abstract: The study is aimed at clarifying the elastic and inelastic behaviour of irregular panel zones (PZs) in a steel moment-resisting frame with circular hollow section (CHS) steel columns and H-shape steel beams connected with external diaphragm under cyclic loading, where the elevations of the beams on left- and right-hand sides of the column are different. To this end, experiments were carried out on the beam-to-column steel sub-assemblage frame connected with an external diaphragm. A parametric study was conducted by considering different values of a parameter β (the ratio of the elevation difference of the beams on both sides of the column to the beam height), and different configurations of the external diaphragm in the connection. The experimental results revealed that the parameter β has a significant influence on the stiffness of the PZs, but no significant effect on the shear strength of the PZs, and the stiffness of the PZs decrease as β increases. In addition, the shape of the external diaphragm has significant influences on the energy dissipation capacity and load bearing capacity of the frame. A qualitative evaluation of the mechanical performance of the PZs is given, and a reasonable connection configuration for the structure design with the PZs is provided. The non-linear finite element analysis (FEA) method was also used to analyze the test specimens. By comparing with the experimental results, the FEA method can give a reference for quantitative analysis of the mechanical properties of the irregular PZs. Highlights: The elastic and inelastic behavior of irregular PZs in a steel moment-resisting frame is experimentally tested. The elevation difference of the beams on both sides of the column has little influence on the PZs shear strength. The elevation difference of the beams on both sides of the column has a significant effect on the PZs initial stiffness. The configurations of the external diaphragm should be designed carefully to improve energy dissipation capacity.